Analyzing Factors Shaping Amanda Brownies Consumers' Purchase Decisions: Menganalisis Pengaruh Citra Merek, Kualitas Produk, dan Harga pada Keputusan Pembelian Konsumen: Studi Kuantitatif pada Konsumen Amanda Brownies - Moch Agung Kurniawan; Lilik Indayani (Academia Open, 2023)
This research aims to investigate the partial and simultaneous effects of brand image, product quality, and price on the purchasing decisions of Amanda brownies consumers in Sidoarjo, employing a quantitative survey method and utilizing the SPSS application for data analysis. The study adopts an accidental sampling technique to determine the respondents and collects data through online questionnaires distributed via Google Forms. The findings provide insights into the significant influence of brand image, product quality, and price on consumer purchasing decisions. The implications of this research offer valuable recommendations for marketers and businesses in enhancing their strategies to attract and retain consumers, while also contributing to the broader field of consumer behavior research. Highlight: Brand image: Influence on consumer perception and loyalty. Product quality: Key determinant of consumer satisfaction and repeat purchases. Price: Impact on consumer affordability and perceived value. Keywords: Brand image, Product quality, Price, Consumer purchasing decisions, Amanda Brownies